Representation, Relation and 'Empêchement': Aesthetic Affinities in Beckett's Dialogues with Georges Duthuit. Issue 2 (September 2016) - Lawrence, Tim
Abstract : This essay examines Samuel Beckett's correspondence with Georges Duthuit between 1948 and 1950, the period when Duthuit edited Transition with Beckett's close involvement. By contrast to most discussions of Beckett's relationship with Duthuit, the essay focuses on Duthuit's perspective in these exchanges. It argues that Duthuit's assimilation of philosophical perspectives, especially those given in Maurice Merleau-Ponty's Phénomenologie de la perception and Maurice Blanchot's Thomas l'obscur, were influential for Beckett's own thinking about aesthetics. This thinking is present in Three Dialogues with Georges Duthuit (1949), which I argue draws on Duthuit's side of the exchanges more positively than is typically assumed, and I trace how Duthuit's letters to Beckett actively respond to a theory of 'empêchement' – a resistance to representation – expressed in Beckett's earlier art criticism. Moreover, the essay argues that Duthuit's monograph Les Fauves, and its translation as The Fauvist Painters supervised by Beckett, bear the traces of Duthuit's exchanges with Beckett, and foreshadow the particularity of Beckett's visual aesthetic in mature prose such as L'Innommable . In this essay, I therefore add to the material challenging the 'siege in the room' narrative of Beckett as an isolated writer during the post-war period, and also suggest that translation, criticism and correspondence offered a way for both men to work through and engage with specific philosophical ideas subtly present in Beckett's post-war writing.